2019
DOI: 10.4013/base.2019.163.02
|View full text |Cite
|
Sign up to set email alerts
|

IFRS adoption and company conservatism in Colombia and Brazil

Abstract: Este é um artigo de acesso aberto, licenciado por Creative Commons Atribuição 4.0 Internacional (CC BY 4.0), sendo permitidas reprodução, adaptação e distribuição desde que o autor e a fonte originais sejam creditados.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
0
0
Order By: Relevance
“…Therefore, it is observed that in 11 of the 12 companies analyzed, the level of conservatism is maintained. These results partially agree with the research developed by Pelucio et al (2019).…”
Section: Resultssupporting
confidence: 93%
“…Therefore, it is observed that in 11 of the 12 companies analyzed, the level of conservatism is maintained. These results partially agree with the research developed by Pelucio et al (2019).…”
Section: Resultssupporting
confidence: 93%
“…En esta línea, a nivel de Colombia, los estudios han explorado el efecto patrimonial del proceso de convergencia, el cambio en diferentes indicadores financieros, el comportamiento del costo de capital y el valor en bolsa de las empresas, la liquidez del mercado bursátil, el grado de conservadurismo, la 76 comparabilidad y la relevancia informativa y valorativa. Las conclusiones muestran avances importantes en la divulgación de la información financiera (comparabilidad y relevancia informativa), pero también se ha evidenciado una baja incidencia en temas asociados al uso efectivo que los agentes económicos hacen de esta (relevancia valorativa y costo de capital) (Bedoya y Giraldo, 2018;Lasso et al, 2018;Ruano et al, 2018;Laverde et al, 2019;Pelucio et al, 2019;Rico et al, 2020;Ruiz et al, 2020;Católico, 2021;Rico, 2022;Vergara et al, 2023).…”
Section: Introductionunclassified